Implementation of islamic education in leadership character building and islamic management in madrasah students (Case study at Darunnajah Islamic Boarding School). - Wiji Lestari1; Ahmad Sulthoni; Syahlarriyadi (Journal of Islamic, Social, Economics and Development, 2024)
In the midst of leadership crisis challenges at the local and national levels, the Muslim community faces an urgent need for prospective leaders with integrity and Islamic character. History records many great figures, such as Sutan Syahrir, Buya Hamka, and General Sudirman, who have demonstrated strong and visionary non-formal leadership. However, currently, it is difficult to find national leadership figures who were born from Islamic boarding school circles. Great hopes are now focused on Islamic educational institutions, especially Islamic boarding schools, which have great potential in producing future leaders. This research examines the implementation of the education system at the Darunnajah Islamic Boarding School, which has adopted the concept of The 7 Habits of Highly Effective People from Stephen R. Covey. This approach is in line with Islamic teachings and leadership inspired by Indonesian Muslim figures. By dividing education into junior and senior phases, this Islamic boarding school focuses on developing character, personal habits, as well as leadership and management skills. Senior students at Darunnajah are given responsibility for managing Islamic boarding school life, which is a place for them to develop leadership, management skills and problem-solving abilities. This system aims to produce future leaders who are not only competent, but also have a strong foundation of Islamic character. The conclusion of this research confirms that the problem-solving-based approach applied at Darunnajah has great potential in producing quality leaders. The implication of these findings is the importance of continuous evaluation in the Islamic education system in order to strengthen leader cadre formation. It is hoped that future research can further